2009
DOI: 10.4161/psb.4.8.9229
|View full text |Cite
|
Sign up to set email alerts
|

Plant age and genotype impact the progression of bacterial community succession in the Arabidopsis rhizosphere

Abstract: The rhizosphere is strongly influenced by plant-derived phytochemicals exuded by roots and plant species exert a major selective force for bacteria colonizing the root-soil interface. We have previously shown that rhizobacterial recruitment is tightly regulated by plant genetics, by showing that natural variants of Arabidopsis thaliana support genotype-specific rhizobacterial communities while also releasing a unique blend of exudates at six weeks post-germination. To further understand how exudate release is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(118 citation statements)
references
References 18 publications
3
102
0
1
Order By: Relevance
“…While these studies demonstrated that plant microbial communities change in response to plant development they were not able to distinguish how or which microbes contribute to the changes observed. For example, Micallef et al (2009a) through denaturing gradient gel electrophoresis analysis observed that Arabidopsis rhizosphere microbial communities varied with plant development and that microbial communities in early plant development were more distinct to the bulk soil and that this difference decreased with plant age. Similarly, an assessment of the potato rhizosphere demonstrated that young potato plants showed cultivar-dependent rhizosphere microbial communities but these differences in the microbiomes disappeared as the plants aged (Inceoglu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies demonstrated that plant microbial communities change in response to plant development they were not able to distinguish how or which microbes contribute to the changes observed. For example, Micallef et al (2009a) through denaturing gradient gel electrophoresis analysis observed that Arabidopsis rhizosphere microbial communities varied with plant development and that microbial communities in early plant development were more distinct to the bulk soil and that this difference decreased with plant age. Similarly, an assessment of the potato rhizosphere demonstrated that young potato plants showed cultivar-dependent rhizosphere microbial communities but these differences in the microbiomes disappeared as the plants aged (Inceoglu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we tested this hypothesis by analyzing the rhizosphere microbial composition of Arabidopsis by 454 pyrosequencing at four distinct physiological stages of development: seedling (four-five leaf stage), vegetative (rosette), bolting and flowering. We did not include samples past the flowering stage because previous studies have determined that rhizosphere microbial communities converge past the flowering stage (Micallef et al, 2009a;Lundberg et al, 2012). Further, a metatranscriptomics analysis of the rhizomicrobiome was also conducted to ascertain a relationship between plant growth and microbiome functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizodeposits are composed of sugars, amino acids, organic acids, fatty acids, proteins, ions, secondary metabolites, mucilage, water, and miscellaneous carbon-containing compounds (Bais et al 2006;Dennis et al 2010). Significant evidence accumulated over the years indicates that the composition of root microbial communities is influenced, in large part, by the plant species and its developmental stage (Micallef et al 2009;Mougel et al 2006;Weisskopf et al 2006). Indeed, an intricate coevolution of plants and rhizosphere microbial communities was suggested by the observation that resident plants or their root exudates are capable of maintaining the biomass and diversity of soil fungal communities to a much greater extent than nonresident or introduced plants ).…”
mentioning
confidence: 99%
“…Differences in morphological and physiological features of roots among sugarcane cultivars may exist, as reported for the uptake capacity per unit of dry matter and for root branching, suggesting differences in the efficiency of C allocation and in acquisition of water and nutrients among sugarcane genotypes . Additionally, other studies have shown differences in the soil microbiota due to the plant genotype and its rhizospheric effect (Marschner et al, 2006;Schweitzer et al, 2008;Micallef et al, 2009). Changes in the structure of the microbial community and functional diversity due to plant genotype were also observed by Dunfield and Germida (2001) analyzing fatty acid profiles and C-substrate utilization in the rhizosphere of brassica spp.…”
Section: Discussionmentioning
confidence: 80%